A new classification of interphase nuclei based on spatial organizations of chromosome 8 and 21 for t(8;21) (q22;q22) acute myeloid leukemia by three-dimensional fluorescence in situ hybridization. Issue 12 (December 2015) - Tian, Xueli; Wang, Yanfang; Zhao, Fengying; Liu, Jinlin; Yin, Jun; Chen, Dieyan; Ma, Wanyun; Ke, Xiaoyan
Highlights: We studied spatial organizations of chromosome 8 and 21 for AML-M2 by 3D-FISH. Nuclei were classified into normal, transitional, and malignant nuclei. Occurrences of each type nuclei were associated with the disease progression. d / R of chromosome 8 was similar to d / R of chromosome 21 for relapse sample. Centers of close chromosomal pairs were more internal than normal pairs. Abstract: Interphase heterogenous chromosomes spatially close to each other are predominantly located near the center of nuclei and are prone to incur translocations. We screened a t(8;21) (q22;q22) acute myeloid leukemia-M2 patient during three phases (post-chemotherapy, remittent stage, and relapse) and a donor of normal karyotype as control by two-(2D) and three-dimensional (3D)-fluorescence in situ hybridization (FISH). Our classification of nuclei (normal, transitional, and malignant nuclei) by 3D-FISH analyses may provide a more precise prognosis than 2D-FISH results, especially for remittent stage sample in our study, in which 2D-FISH findings showed normal results, whereas 3D-FISH results showed extreme abnormalities (normal nuclei 27%, transitional nuclei 36%, malignant nuclei 37%). The relative radial positions ( d / R ) of chromosomes 8 were similar to d / R of chromosomes 21 for the relapse sample. We classified heterogenous chromosome pairs into close pairs and normal pairs based on their relative distances ( d′ /(2 R )). The centers of close pairs were more internal than normal pairs in nuclei in all samples, and the d / R values of a given-type pairwise heterogenous chromosomes were similar among four samples. Our data demonstrate that the classification of nuclei based on spatial organization of chromosomes by 3D-FISH is reasonable and essential for evaluating acute myeloid leukemia prognosis.